(untitled) (Diametros, 2013)
The paper focuses on a discussion about McDowell’s "conceptualist" interpretation of Kant’s theory of experience, as one in which all representational content is identified with conceptual content. Both in Mind and WorldM and in his Woodbridge Lectures, McDowell furthers a reading on which the "picture of visual experiences as conceptual shapings of visual consciousness is already deeply Kantian", supporting it with Kant’s famous claim from the A51/ B75 passage of the Critique of Pure Reason, which can be called a Cooperation Thesis. However, much indicates that McDowell’s reading is, if not altogether false, then at least one-sided. In the "Transcendental Aesthetic", as well as in some of the pre-Critical writings (Concerning the ultimate foundation of the differentiation of regions in space or the "Inaugural Dissertation"), Kant presented a range of arguments for a subjective, non-discursive character of space and time, i.e. the forms of sensible intuition and pure intuitions themselves, underlying all conceptual cognition, and providing a non-conceptual basis for a special kind of synthetic a priori cognition (geometry). This allows us to conclude that he would rather take the side of the contemporary “nonconceptualists”, and could be regarded as their predecessor, to use R. Hanna’s formulation. On this reading of the Kantian theory of empirical cognition, intentionality is independent of and prior to any application of concepts to the objects of experience.